Aviation Dentistry: Preflight Dental Check on The Fighter Pilots - Hatta, Ridhayani; Budiman, Mohamad Arif (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2026)
Aviation dentistry is a specialized field that addresses oral and maxillofacial health in environments subject to significant changes in atmospheric pressure, particularly during flight. Barodontalgia, a form of dental pain triggered by such pressure fluctuations, can adversely affect pilots' performance, potentially impairing mission success. This narrative review critically assesses the necessity of preflight dental evaluations for military fighter pilots as a preventive measure against barodontalgia-related in-flight complications. A comprehensive literature search was conducted across PubMed, Web of Science, and Google Scholar for studies published between 2020 and 2025. A total of 55 records were identified, and 23 studies were included in the final qualitative analysis. Findings indicate that barodontalgia is often precipitated by pre-existing dental conditions, such as untreated caries, pulpitis, and unstable restorations, which become exacerbated under high-altitude pressure changes. Fighter aircraft commonly operate at altitudes between 45,000 and 51,000 feet, with rapid pressure fluctuations that can significantly worsen dental symptoms. Despite the recognition of barodontalgia’s operational impact, preflight dental assessments are not routinely integrated into current aeromedical protocols. The review recommends formalizing a Dental Requirements Document as part of military preflight checks, including comprehensive dental health evaluations and history assessments. Such a protocol could mitigate the risk of dental emergencies during flights and enhance operational safety by ensuring dental readiness before missions.